Pengaruh Faktor Internal Dan Eksternal Terhadap Kinerja Sumber Daya Manusia Pada Pabrik Kontruksi Beton - Nawang Aji Sasongko; Yulvi Zaika; Agus Suharyanto (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2017)
This study aims to determine the factors that affect the performance of human resources in the factory of PT. Wijaya Karya Beton PPB Pasuruan. From all these factors will be searched the most dominant factors that influence and then proceed with corrective action. Research is needed to do to find out what are the factors that highly affect the performance of human resources, more expecialy on the human resources factory. The method used is SEM method and IPA analysis. SEM analysis is used to find out that are the factors that higher affect the performance of factory human resources. While the IPA analysis, used to determine the step of improving human resource management in the implementation of the next project. The sampling of the research was conducted by distributing questionnaires to the entire population of permanent factory employees with 35 respondents. External factors of HR are known to be a factor that is very influential on the performance of factory HR, compared with internal factors. This is evident from the SEM analysis, where internal HR factors are more dominant in affecting the HR performance of the project, especially those associated with coworkers and resources of permanent employees.